The Therapeutic Gospel for the Traumatic World. Stigmata Domini Iesu Christi in Corpore as the Crown of Victory - Chan, Jimmy (Vox Patrum, 2024)
Drawing on Augustine’s Epistolae ad Galatas Expositionis Liber Unus, I would like to explore two insights into the therapeutic understanding of persona trauma. First, for Augustine, Paul’s past turbulentas contentiones are not in and of themselves stigmata domini Iesu Christi. What, then, is the meaning and significance for Augustine of Paul’s statement “For I bear the marks of the Lord Jesus Christ in my body” (Gal 6:17)? Secondly, Augustine recognizes that Paul has been fighting his “alios conflictus et certamina”. What is his struggle and how does it relate to the stigmata of the Lord Jesus Christ in the body? In traumatic experiences, our hearts may be troubled by the guilt of the traumatic experiences (for example, by asking questions like: “Did I do something wrong to cause this?”). Paul is able to recognize and reject anyone (or anything) that might tempt him to return to the accusation of the law, hence the declaration: “De cetero, inquit, laborem nemo mihi praestet”. I argue that by interpreting the metaphorical sense of ad coronam uictoriae proficiebant, Augustine pronounces Christ’s victory on the Cross over sin and death by explaining Paul’s proclamation of his hermeneutic of Christ’s stigmata. Through this soteriological lens, Augustine brings his interpretation of Galatians to its climax by proclaiming “Gratia domini nostri Iesu Christi cum spiritu uestro, fratres, Amen” (Gal 6:18).